The Night and Day of Amihud's (2002) Liquidity Measure. (1st March 2021) - Barardehi, Yashar H; Bernhardt, Dan; Ruchti, Thomas G; Weidenmier, Marc
Abstract: Amihud's stock (il)liquidity measure averages daily ratios of the absolute close-to-close return to dollar volume, including overnight returns. Our modified measure uses open-to-close returns matching return and trading volume measurement windows. It is more strongly correlated with trading-cost measures (by 8%–37%) and better explains cross-sections of returns, doubling estimated liquidity premiums. Using nonsynchronous trading near close, we show overnight returns are primarily information driven: including them in Amihud's proxy for price impacts of trading magnifies measurement error, understating liquidity premiums. Our modification helps wherever Amihud's measure is required. Our measures are publicly available for 1964–2019 and can be updated. ( JEL G12, G14) Received June 2, 2020; editorial decision September 11, 2020 by Editor Jeffrey Pontiff.